1976
DOI: 10.1007/bf00399451
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the neoagarotetra-ase and neoagarobiase of Cytophaga flevensis

Abstract: The degradation of neoagarotetraose and neoagarobiose by Cytophaga flevensis was investigated. The organism possesses an enzyme that hydrolyzes the tetramer by cleavage of its central beta-galactosidic linkage. The product of this reaction, neoagarobiose, is further hydrolyzed enzymatically to D-galactose and 3,6-anhydro-L-galactose. Both enzyme activities were localized in the cytoplasm. Attempts were made to partially purify the respective enzymes and although a 30-40 fold-purification was achieved, the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Data of three independent experiments were expressed as mean ± standard deviation. Asterisk indicates a significant difference (p<0.05) compared with the untreated control Cytophaga flevensis (Day and Yaphe 1975;Sugano et al 1994;Van Der Meulen and Harder 1976). However, the industrial application of these NABHs was not possible since their amino acid sequences were not yet fully discovered.…”
Section: Discussionmentioning
confidence: 90%
“…Data of three independent experiments were expressed as mean ± standard deviation. Asterisk indicates a significant difference (p<0.05) compared with the untreated control Cytophaga flevensis (Day and Yaphe 1975;Sugano et al 1994;Van Der Meulen and Harder 1976). However, the industrial application of these NABHs was not possible since their amino acid sequences were not yet fully discovered.…”
Section: Discussionmentioning
confidence: 90%
“…Agar-agar can be degraded by several bacterial strains from marine environments and other sources. Agarolytic bacteria are ubiquitous in coastal and estuarine regions; however, they are not exclusively autochthonous in the marine environment, since some reports have shown that they also occur in freshwater, sewage and soil (von Hoffsten and Malmqvist 1974;van der Meulen et al 1976;Agbo and Moss 1979). Some of bacteria isolates have been identified and classified in to Actinomyces, Agarivorans, Alterococcus, Alteromonas, Microbulbifer, Cellulophaga, Cytophaga, Streptomyces, Vibrio, Pseudomonas, Saccharophagus, Pseudoalteromonas, Zobellia, and Bacillus (Macian et al 2001;Yoon et al 1996;Jean et al 2006;Khambhaty 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial agarases are endohydrolases that cleave large agar molecules and thereby generate an increasing molar quantity of saccharides with decreasing average size. Only oligoagars that are not larger than tetraose can be further degraded in the bacterial periplasmic space and assimilated by the cell (Turvey and Christison 1967, Day and Yaphe 1975, Van der Meulen and Harder 1976, Sugano et al 1994). This may theoretically result in an initial accumulation of oligoagars that are larger than tetraose, before their assimilation.…”
mentioning
confidence: 99%